ORGANIZATIONAL ENTREPRENEURSHIP FORMS AND ENTREPRENEURSHIP: RURAL POPULATION AWARENESS (INNOVATIVE ECONOMY, 2019)
Hubeni Yu.E. ORGANIZATIONAL ENTREPRENEURSHIP FORMS AND ENTREPRENEURSHIP: RURAL POPULATION AWARENESSPurpose. The aim of the article is determination of the state of awareness of certain economically active groups of the population by professional knowledge about the content and components of entrepreneurship, in particular about the essence and peculiarity of main organizational legal forms of its realization.Methodology of research. The article is published on the basis of empiric data received while making some applied academic and research projects. The projects were made in villages of Lviv region. According to the content and methods of fulfilling the projects were isolated. Some researchers were of out-of-project character. The monographic method and methods for comparing, synthesizing and analyzing data from the results of a survey of individual population groups on the essence and peculiarity of main organizational legal forms of its realization was applied in this publication.Results. It is established that rural population of Lviv region, its active in terms of economy groups, in particular, are informed enough of the content, components and consequences of entrepreneurship activity. In general, entrepreneurship awareness of village dwellers is increasing, and uncertainty is decreasing. The students of agrarian higher educational institutions are rather well-oriented as for entrepreneurship content and components, though the students of engineering branch have some higher level of orientation. The awareness of active in terms of economy villagers, concerning widely spread organizational entrepreneurship forms, is studied. Particularly, sufficient level of knowledge concerning farms, some companies and private entrepreneurs is established. Less spread or complicated forms of entrepreneurship are unknown among village dwellers.Originality. Informational awareness level of the content and peculiarities of main organizational entrepreneurship forms by rural population is established for the first time. The necessity of available ways of informing and economic educating for the citizens to perceive is substantiated.Practical value. Research results have practical significance for forming informational and educational companies dealing with organizational entrepreneurship forms in rural area.Key words: information; entrepreneurship; organizational and legal forms; private business; rural dwellers.
Keywords: Key words; information; entrepreneurship; organizational and legal forms; private business; rural dwellers.